2018
DOI: 10.1103/physrevlett.120.265501
|View full text |Cite
|
Sign up to set email alerts
|

Negative Hydration Expansion in ZrW2O8 : Microscopic Mechanism, Spaghetti Dynamics, and Negative Thermal Expansion

Abstract: We use a combination of x-ray diffraction, total scattering, and quantum mechanical calculations to determine the mechanism responsible for hydration-driven contraction in ZrW_{2}O_{8}. The inclusion of H_{2}O molecules within the ZrW_{2}O_{8} network drives the concerted formation of new W─O bonds to give one-dimensional (─W─O─)_{n} strings. The topology of the ZrW_{2}O_{8} network is such that there is no unique choice for the string trajectories: the same local changes in coordination can propagate with a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…The rigidity constraints could allow chiral motions of the Zr atoms and of the non-bridging O atoms on the WO 4 tetrahedra. For example, a revolution of a terminal O atom would bring it closer in turn to each of the three equivalent positions where it could form a W-O-W bond [55]. As the terminal O atoms are permitted by network topology and crystallographic symmetry to undergo chiral revolutions, it would not be surprising to find such modes with the methods used here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rigidity constraints could allow chiral motions of the Zr atoms and of the non-bridging O atoms on the WO 4 tetrahedra. For example, a revolution of a terminal O atom would bring it closer in turn to each of the three equivalent positions where it could form a W-O-W bond [55]. As the terminal O atoms are permitted by network topology and crystallographic symmetry to undergo chiral revolutions, it would not be surprising to find such modes with the methods used here.…”
mentioning
confidence: 99%
“…The chiral modes found in α-BiB 3 O 6 are distinct from the RUMs which have been used successfully to understand NTE in some materials [10]. However, the RUM model has been found to not apply to many NTE materials, either because of overconstrained coordination polyhedra [53], or because the polyhedra simply are not rigid [54,55]. In materials where the RUM model fails, the origins of NTE often remain incompletely understood, and it is possible that, for chiral systems, calculations of mode circular polarizations could bring additional clarity.…”
mentioning
confidence: 99%
“…However in some cases, even small molecules can ingress in formally nonporous dense framework materials. Recently, Goodwin 20% more dense [79]. Examination of the correlated translation, rotation and distortion of ZrO 6 /WO 4 study identified "spaghetti-like" displacements of a W O W network which are responsible for NHE in this material.…”
Section: Adsorption-induced Contractionmentioning
confidence: 87%
“…Recently, Goodwin and coworkers described negative hydration expansion (NHE) in zirconium tungstate, Zr 2 W 2 O 8 . Though nonporous, this structure can be reversibly hydrated to Zr 2 W 2 O 8 · H 2 O, transforming to a disordered phase that is 20% more dense [91]. Examination of the correlated translation, rotation and distortion of ZrO 6 /WO 4 study identified "spaghetti-like" displacements of a W−O−W network which are responsible for NHE in this material.…”
Section: Adsorption-induced Contractionmentioning
confidence: 91%